Orientalism And Its Impact On Contemporary Islamic Reformist Thought” (Islamic Sciences Journal, 2025)
The phenomenon of Orientalism is one of the significant issues that thinkers, scholars, and intellectuals should study and thoroughly examine, as it poses a serious threat to the Arab-Islamic society in terms of the constraints and boundaries set by Allah for Muslims. In today’s world of rapid technological development, social media, and the internet, there is a major danger to individuals and communities from Orientalists and their allies, as they spread poison and doubts in the minds of the general public. In recent times, this direct influence has become evident. From this standpoint, the study of Orientalism began by defining its concept and examining its impact on contemporary reformist thought, as well as how to respond to the doubts raised by Orientalists and enhance critical thinking within Islamic societies. The study also focuses on the issues emphasized in Orientalist research and clarifies them.
Keywords: Orientalism, the influence of Orientalism on reformist thought, skepticism of Orientalists , feeding suspicions , issues of Orientalism Research